2018
DOI: 10.1021/acsearthspacechem.8b00156
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric β-Caryophyllene-Derived Ozonolysis Products at Interfaces

Abstract: By integrating organic synthesis, secondary organic aerosol synthesis and collection, density functional theory (DFT) calculations, and vibrational sum frequency generation (SFG) spectroscopy, we identify close spectral matches between the surface vibrational spectra of β-caryophyllene-derived secondary organic material (SOM) and those of β-caryophyllene aldehyde and β-caryophyllonic acid at various interfaces. Combined with the record high surface tension depression described previously for these same oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…The selection of these standard species was informed by previous work targeting similar sample types, using the same instrumentation (Worton et al, 2011;Zhang et al, 2018), and covers species including sugars, polycyclic aromatic hydrocarbons (PAHs), and both monoterpene and isoprene oxidation products. In addition to commercially available external standards, six sesquiterpene oxidation products were custom synthesized by collaborators (as described in Bé et al, 2019), for expanded coverage of potentially important chemical tracers. The full list of standard components can be found in Table A1, and the standard property distribution in volatility-polarity space is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of these standard species was informed by previous work targeting similar sample types, using the same instrumentation (Worton et al, 2011;Zhang et al, 2018), and covers species including sugars, polycyclic aromatic hydrocarbons (PAHs), and both monoterpene and isoprene oxidation products. In addition to commercially available external standards, six sesquiterpene oxidation products were custom synthesized by collaborators (as described in Bé et al, 2019), for expanded coverage of potentially important chemical tracers. The full list of standard components can be found in Table A1, and the standard property distribution in volatility-polarity space is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Phase-resolved measurements here are based on the internal heterodyne method, where a freshly cleaned z -cut α-crystalline quartz window was used as a substrate instead (see the SI). ,, In summary, when the vSFG spectrum of a sample on the z -cut α crystal quartz surface is measured, the vSFG response has contributions from the bulk of the z -cut α quartz crystal (internal local oscillator) and from the molecules adsorbed on the quartz crystal surface. A detailed phase-resolved SFG study by Wang et al showed the application of the internal heterodyne method by utilizing the azimuthal angle phase dependence of the right-handed z -cut α quartz crystal. , In our experiment, carbaryl I ± x Norm SSP and PPP spectra on quartz were obtained at azimuthal angles of Φ = 0° (+ x axis) and Φ = 180° (− x axis) by a 15 s acquisition and normalized to nonresonant response of the bare z -cut α quartz crystal under the + x direction (see the SI).…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Here, we primarily focus on the interfacial structure and the surface anchoring mechanism of carbaryl on silica using a combination of surface-selective nonlinear vibrational spectroscopy and computational modeling, including molecular dynamics (MD) simulations and ab initio calculations of vibrational spectra. Raman and Fourier transform infrared (FTIR) vibrational spectroscopic methods have been widely applied to study pesticides in bulk solutions and films. , Here, we apply vibrational sum frequency generation (vSFG) spectroscopy, an in situ technique particularly suitable for the analysis of molecules at buried interfaces and sensitive to sub-monolayer amounts of adsorbates. ,, As a coherent nonlinear spectroscopic technique, the vSFG response is highly sensitive to molecular orientation and ordering at the surface, , making vSFG a powerful technique for obtaining detailed chemical information regarding the molecular composition, structure, and interactions of molecules at interfaces. As such, it has become a versatile tool for studies of environmental surfaces and interfaces under ambient conditions ,, and for revealing structure–activity relationships of surface-immobilized compounds, like antimicrobial coatings. …”
Section: Introductionmentioning
confidence: 99%
“…21 Dissolved organic matter and surface-active organic compounds also modify the hygroscopicity and surface tension of the particles, and hence their propensity to act as cloud condensation nuclei. 22,23 The coating of aqueous droplet surfaces by surfactant organic molecules inhibits dissolution of ambient gases including CO2 with consequences for the droplet pH. 24 Microbe metabolism can change the organic composition of cloud and aerosol droplets, but the density of metabolically active cells in the atmosphere is low.…”
Section: Virtual Issue In Atmospheric Chemistry Researchmentioning
confidence: 99%